Market niches for increased small ruminant production in southern Nigeria - Jabbar, M.A. (International Livestock Research Institute, 1998)
The humid zone of southern Nigeria has an estimated 9 million small ruminants, largely consisting of trypanotolerant dwarf goats and sheep. In spite of this, aggregate demand for small ruminant meat in the zone exceeds supply from local sources and the gap is met by supplies from the subhumid and semi-arid zones in the north of the country. Such supply-demand imbalance has important implications for increased small ruminant production in the humid zone. This study examines the scope for such increased production in southern Nigeria using data from a year-long survey of selected rural markets in south-west and south-east Nigeria.